2016
DOI: 10.1016/j.celrep.2016.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Dynamics in the Frontoparietal Attention Network during Sustained Attention in the Ferret

Abstract: Summary Sustained attention requires the coordination of neural activity across multiple cortical areas in the frontoparietal network, in particular prefrontal cortex (PFC) and posterior parietal cortex (PPC). Previous work has demonstrated that activity in these brain regions is coordinated by neuronal oscillations of the local field potential (LFP). However, the underlying coordination of activity in terms of organization of single unit (SU) spiking activity have remained poorly understood, particularly in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 50 publications
(58 reference statements)
3
31
0
Order By: Relevance
“…For instance, Spyropoulos et al (Spyropoulos et al, 2018) recently reported that theta oscillations in the visual cortex elicited by visual stimuli decreased in amplitude when visual attention was directed. In addition, another recent study found arousal-reduced theta power in the high-order visual area (i.e., posterior parietal cortex) of the ferret brain (Stitt et al, 2018) despite its enhanced long-range theta synchrony with the prefrontal cortex during sustained attention reported by an earlier study (Sellers et al, 2016). In fact, a pioneering neuro-feedback study in the 1970s reported similar results of an association between occipital theta suppression and improved performance in a visual detection task (Beatty et al, 1974).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…For instance, Spyropoulos et al (Spyropoulos et al, 2018) recently reported that theta oscillations in the visual cortex elicited by visual stimuli decreased in amplitude when visual attention was directed. In addition, another recent study found arousal-reduced theta power in the high-order visual area (i.e., posterior parietal cortex) of the ferret brain (Stitt et al, 2018) despite its enhanced long-range theta synchrony with the prefrontal cortex during sustained attention reported by an earlier study (Sellers et al, 2016). In fact, a pioneering neuro-feedback study in the 1970s reported similar results of an association between occipital theta suppression and improved performance in a visual detection task (Beatty et al, 1974).…”
Section: Introductionmentioning
confidence: 78%
“…It should be noted that the substantial work conducted in the frontal cortex has found gamma oscillations to play an important role in pro-cognitive functions (Cho et al, 2015; Kim et al, 2016). On the neuronal spike levels, the spiking activities of the frontal cortex in the high gamma band were locked to theta oscillations in the frontal and posterior parietal cortices during sustained attention (Sellers et al, 2016). In our study, we found effective modulation of low gamma, but not high gamma, by frontal theta using cross-frequency coupling analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that the 5-CSRTT engaged synchrony of oscillatory activity in the frontoparietal network of the ferret [16,17]. Phase synchronization both at the microscale of neuronal action potentials and the mesoscale of the population synaptic activity reflected in the local field potential was elevated in the theta-frequency range.…”
Section: Introductionmentioning
confidence: 92%
“…After successful training, the ferrets were surgically implanted with a chronic multichannel electrode array (2x8 tungsten electrode array, 250µm spacing, low-impedance reference electrode with the same length on the same array, MicroProbes Inc, Gaithersburg, MD) in LP/Pulvinar. Surgical procedure was similar to those previously described [16,22]. Briefly, ferrets were first injected with ketamine/xylazine (30 mg/kg of ketamine, 1-2 mg/kg of xylazine, IM) for anesthesia induction, and then were intubated and anesthetized with inhaled isoflurane (1.5-2%) in 100% medical oxygen (mechanically ventilated, 10-11 cc volume, 50 bpm).…”
Section: Surgerymentioning
confidence: 99%